Answer:
(10, - 9 )
Step-by-step explanation:
Given the 2 equations
y = - 2x + 11 → (1)
y = - 3x + 21 → (2)
Substitute y = - 2x + 11 into (2)
- 2x + 11 = - 3x + 21 ( add 3x to both sides )
x + 11 = 21 ( subtract 11 from both sides )
x = 10
Substitute x = 10 into either of the 2 equations and evaluate fir y
Substituting into (1)
y = - 2(10) + 11 = - 20 + 11 = - 9
solution is (10, - 9 )
Hey!
------------------------------------------------
Solution:
We can get two different ways of 1:6 by add +1:+6.
1 + 1 = 6 + 6
2:12
2 + 1 = 12 + 6
3:18
------------------------------------------------
Answer:
2:12 and 3:18
------------------------------------------------
Hope This Helped! Good Luck!
The Correct answer is
(n)(4) = (7)(8)
4n = 56
n = 14
B or 12 would be the correct choice!
Hope this helps and mark as brainliest please!